If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -0.8) = 4x + -4 Reorder the terms: 3(-0.8 + x) = 4x + -4 (-0.8 * 3 + x * 3) = 4x + -4 (-2.4 + 3x) = 4x + -4 Reorder the terms: -2.4 + 3x = -4 + 4x Solving -2.4 + 3x = -4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -2.4 + 3x + -4x = -4 + 4x + -4x Combine like terms: 3x + -4x = -1x -2.4 + -1x = -4 + 4x + -4x Combine like terms: 4x + -4x = 0 -2.4 + -1x = -4 + 0 -2.4 + -1x = -4 Add '2.4' to each side of the equation. -2.4 + 2.4 + -1x = -4 + 2.4 Combine like terms: -2.4 + 2.4 = 0.0 0.0 + -1x = -4 + 2.4 -1x = -4 + 2.4 Combine like terms: -4 + 2.4 = -1.6 -1x = -1.6 Divide each side by '-1'. x = 1.6 Simplifying x = 1.6
| 3x-21-7x+20= | | 1+2/x+5/x^2=0 | | 1/2+9/x=5/4 | | 10-2p=4q | | 12-3p=q | | 3x+16x=95 | | 7-2(1-3s)=35 | | -21+[-14+(-13)]= | | 15-p=q | | 4(4+2x)=7(x-2) | | y=20-10 | | -2p-2(4-4p)=4(p-4)-18 | | z/4=-10 | | m-1/2=-11/12+11/6m | | 36m^2-25/4 | | -23-8c=7(4c+9) | | 7r=-14 | | 3(2+x)=14+x | | 2x+3=55x | | 8x-25=-33+9x | | 11x+(-12y)+(-15x)+9y= | | 2x-1y=-30 | | Q=75-p | | 5.7q-5.2-5.3q=-0.6q-4.5 | | 3x+25-30x=16 | | -a-3a=7(4a-3)+4(6-8a) | | x+2x+(x+10)=166 | | 3(3+x)=17+x | | 16v^2-8v+1= | | 6s-20=4+8s | | y=10+-4x | | 4x+2x=108 |